Optimization of an Irreversible Diesel Cycle: Experimental Results of a Ceramic Coated Indirect-Injection Supercharged Diesel Engine - Parlak, A.; Yasar, H.; Soyhan, H. S.; Deniz, C.; Deniz, Cengiz (American Chemical Society (ACS), 2008)
In this work, an irreversible dual cycle analysis has been performed for enhancing the characteristics of a low heat rejection (LHR) supercharged single-cylinder indirect-injection (IDI) diesel engine. A relation which gives the maximum power (MP) and the corresponding efficiency has been derived analytically. Optimization of the diesel cycle has been performed for power and thermal efficiency with respect to the pressure ratio and temperature ratio. Optimum values of the pressure ratio and cutoff ratio of the diesel cycle, depending on the temperature ratios, have been derived analytically and compared to the results of an experimental study of the LHR engine, whose optimum performance was obtained by increasing the temperature in the combustion chamber. Effects of a ceramic coating on performance and exhaust emissions in the LHR engine have been compared to those obtained from the standard (STD) diesel engine based on the comparison of the STD and the LHR engines for identical airflow and brake mean eff...
Keywords: Engineering